2017
DOI: 10.1097/bpo.0000000000000685
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Postoperative Antibiotics After Percutaneous Pinning of Pediatric Supracondylar Humerus Fractures

Abstract: Level III-therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…Schroeder and colleagues' retrospective study evaluated the effect of postoperative antibiotics in preventing surgical site infections when treating supracondylar humerus fractures with CRPP. 11 The authors reported an overall infection rate of 1.8%, and patients who received postoperative antibiotics did not have a lower rate of surgical site infections (P = .883). 11 Previous studies have provided outcome and complication data for CRPP procedures of upper extremity fractures when preparing the limb using the full-prep technique.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Schroeder and colleagues' retrospective study evaluated the effect of postoperative antibiotics in preventing surgical site infections when treating supracondylar humerus fractures with CRPP. 11 The authors reported an overall infection rate of 1.8%, and patients who received postoperative antibiotics did not have a lower rate of surgical site infections (P = .883). 11 Previous studies have provided outcome and complication data for CRPP procedures of upper extremity fractures when preparing the limb using the full-prep technique.…”
Section: Discussionmentioning
confidence: 88%
“…14 Battle and Carmichael reported an overall infection rate of 7.9% with smooth K-wire fixation in pediatric patients, but the overall major infection rate was 2% with these cases necessitating irrigation and debridement in the operating room. 2 Infection rates following CRPP have also been investigated in the setting of surgical delays 8 and the use of postoperative antibiotics 11 when treating supracondylar humerus fractures. Larson et al retrospectively reviewed Gartland type II supracondylar humerus fractures treated within 24 hours or >24 hours from the time of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of infection after CRPP of SCHFX are very low, with several studies reporting overall infection rates of approximately 2.3% [ 8 , 9 ]. Deep infection, defined as septic arthritis or osteomyelitis, is even more rare, with rates of 0.3%–0.5% [ 6 9 ]. However, noncompliance with instructions can place patients at increased risk for rare complications, as was observed in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient did not receive postoperative antibiotics following her procedure. Schroeder et al retrospectively found a surgical site infection rate of 1.8% in 618 CRPP of SCHFX regardless of whether postoperative antibiotics were administered [ 9 ]. Iobst et al also reported that the majority of their population, 67%, did not receive any antibiotics, pre or post, and they reported no infections in their treatment population of 304 patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies highlighted infection risk after operative repair of a supracondylar humeral fracture; in 1 randomized study, there was no difference in infection risk whether pin care occurred daily, every other day, or weekly, although pain was more frequent with daily pin-site care 96 . From retrospective studies, postoperative antimicrobial use after supracondylar humeral fracture fixation and delay of surgery (>7 days) were not associated with infection risk 97,98 .…”
Section: Pediatric Orthopaedicsmentioning
confidence: 99%